Foraminiferal biostratigraphy and paleoecology of the Aquia Formation near Hanover, Virginia - Seaton, William Joseph (Virginia Polytechnic Institute and State University, 1982)
Foraminifera of the Paleocene Aquia Formation outcropping near Hanover, Virginia were studied in terms of their taxonomy, stratigraphic distribution and abundance. A total of seventy-nine species were described, eight of which have never been reported in the Aquia. Twenty species of planktonic foraminifera were recovered. The basal seven feet of Aquia contains only long ranging Paleocene Foraminifera. In the next two feet of Aquia occurred Globigerina triloculinoides and Globorotalia acuta which overlap in the Middle Paleocene Globorotalia pusilla pusilla Zone and the Late Paleocene Globorotalia pseudomenardii Zone. The next section of Aquia, from nine feet above its base to six feet below the overlying Marlboro Clay, is referred to the Globorotalia pseudomenardii Zone based on the occurrence of Globorotalia aequa and Globigerina triloculinoides. The top six feet of the Aquia and basal one foot of Marlboro Clay contain Globorotalia subbotinae and Globorotalia occlusa placing this section in the Late Paleocene Globorotalia velascoensis Zone. The basal Aquia f oraminif eral fauna is characterized by low species diversity, high morphologic variability in dominant species and large populations suggesting an unstable, marginal marine environment. The upper sections of the Aquia Formation contain faunal associations with higher species diversity, lower dominance and smaller populations indicating a somewhat deeper water, more stable environment. The associated macrofossil communities and local lithologies support these conclusions. A cross-section through the study area reveals offsets in formational boundaries and unusual downdip thickening of the Tertiary section. Accompanying these anomalies are abrupt changes in the course of the Pamunkey River. These data suggests faulting in the study area analogous to the faulted Coastal Plain strata near Fredericksburg, Virginia (Mixon and Newell, 1978), Master of Science